Common Practices in Setting Expenditure Ceilings within National Budgets - Dorotinsky, William (World Bank, Washington, DC, 2016)
Developing a national budget has always entailed a complex set of negotiations between national Government priorities, line ministry priorities, and a national funding envelope. This note explains how to introduce a medium term horizon into a government’s budgeting process, including the key steps involved. It provides guidance on setting aggregate and line ministry ceilings, reviewing experiences from countries with extensive experience of ceilings (for example, Finland, the Netherlands, Sweden, South Korea, Indonesia, Brazil, Australia, and Canada, among others), as well as those that have more recently adopted them. There is no one right way to set expenditure ceilings. Countries tailor expenditure ceilings to meet their specific needs, budget challenges, and capacity constraints. This note presents an iterative approach - starting from annual ceilings and gradually moving toward a medium-term expenditure framework - allowing for procedural, institutional, and organizational learning and adaptation along the way.